2021
DOI: 10.3390/biology11010051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Secondary Sarcopenia: A Comprehensive Literature Review

Abstract: Background: Sarcopenia has been recognized as an inevitable part of aging. However, its severity and the age at which it begins cannot be predicted by age alone. The condition can be categorized into primary or age-related sarcopenia and secondary sarcopenia. Sarcopenia is diagnosed as primary when there are no other specific causes. However, secondary sarcopenia occurs if other factors, including malignancy or organ failure, are evident in addition to aging. The prevalence of secondary sarcopenia is far great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 117 publications
(141 reference statements)
1
17
0
Order By: Relevance
“…4 Secondary sarcopenia includes hypoactivity, disease sarcopenia and nutritional sarcopenia. 5 In Asian countries, the Asian Working Group for Sarcopenia 2019 recommended determining the characteristics of sarcopenia. 6 These criteria include muscle strength, physical function and muscle mass, which can be used to diagnose sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Secondary sarcopenia includes hypoactivity, disease sarcopenia and nutritional sarcopenia. 5 In Asian countries, the Asian Working Group for Sarcopenia 2019 recommended determining the characteristics of sarcopenia. 6 These criteria include muscle strength, physical function and muscle mass, which can be used to diagnose sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the assessment, prevention and treatment of sarcopenia are important in maintaining and restoring the function, especially in older people. [4][5][6] Sarcopenic dysphagia is a disorder of eating and swallowing caused by a loss of muscle mass and muscle strength of the whole body, including muscles involved in swallowing. 7,8 We reported a scoping review of the diagnosis and treatment of sarcopenic dysphagia 7 that showed a reliable and validated diagnostic algorithm was the most widely used method for diagnosing sarcopenic dysphagia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After age 50, muscle mass and strength decrease by 1–2% and 1.5–5% per year, respectively [3]. In contrast, secondary sarcopenia results from conditions such as disease, lack of physical activity, or poor nutrition [4]. Regardless of the type, patients with sarcopenia have an increased risk of falls, fractures, and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%